Inequality in Latin America : breaking with history? - De Ferranti, David M. (Washington, DC : The World Bank, 2004)
With the exception of Sub-Saharan Africa, Latin America and the Caribbean has been one of the regions of the world with the greatest inequality. This text explores why the region suffers from such persistent inequality, identifies how it hampers development, and suggests ways to achieve greater equity.
Includes bibliographical references (p. 351-380) and index.
osc
Loans
Keywords: Inequality; Equality; Social conditions - Caribbean Area; Economic conditions - Latin America; Latin America; Caribbean Area